Pengaruh Kepercayaan, Kemudahan Penggunaan dan Citra Merek terhadap Loyalitas Pelanggan Maxim di Kota Batam - Sihombing, Trisi Elisa; Oktavia, Yunisa (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study investigates the influence of trust, perceived ease of use, and brand image on customer loyalty toward the Maxim online transportation service in Batam City. The growing reliance on mobile-based transportation services highlights the importance of understanding key factors that contribute to sustained customer engagement. The study aims to evaluate how these three variables affect users’ loyalty in a competitive digital marketplace. A descriptive quantitative approach was employed, targeting active Maxim users who have experience using the application. The sample consisted of 204 respondents selected using purposive sampling, with sample size determined by Jacob Cohen’s formula. Data were analyzed through instrument validity and reliability testing, classical assumption testing, and hypothesis testing using multiple linear regression. The results reveal that trust has the highest individual contribution to loyalty (25.5%), followed by perceived ease of use (24.2%) and brand image (21.5%). Together, these variables explain 64.9% of the variance in customer loyalty (R² = 0.649). Both partial and simultaneous tests indicate that all three independent variables significantly and positively affect customer loyalty. These findings underscore the importance of enhancing service transparency, optimizing user interface design, and reinforcing brand image to build long-term customer relationships.